Передача або збирання відомостей, що становлять службову інформацію, зібрану у процесі оперативно-розшукової, контррозвідувальної діяльності, у сфері оборони країни: питання кваліфікації - Горпинюк, Оксана (Видавництво Львівської політехніки, 2019)
The issue of qualification of crimes – state treason, espionage, acts with official information is considered. Different signs of crimes – public relations, information, criminal are named.
Keywords: crime; state secret; espionage; official information; constitutional features; information in the field of defense of the country